CMOS-compatible Ti/TiN/Al refractory ohmic contact for GaAs heterojunction bipolar transistors grown on Ge/Si substrate - Wang, Yue (2022)
In this article, we demonstrate the Ti/TiN/Al (15/50/50 nm) ohmic contact on InGaP/GaAs heterojunction bipolar transistors (HBTs) epitaxially grown on 200-mm Si substrate. We study the rapid thermal annealing (RTA) effect of the metal stack on both n-type InGaAs and p-type GaAs. The dc characteristics of the HBT devices fabricated using the Ti/TiN/Al metal contacts have been analyzed. Contact resistances (R-c)<0.1 Omega. mm for n-InGaAs and 0.8 Omega. mm for p-GaAs can be achieved. A dc current gain of 45 with a collector-base breakdown voltage (BVcbo) of 15.65 V is achieved. The ideality factor of the emitter-base current (n(b)) and base-collector current (n(c)) is 1.03 and 1.44, respectively, after RTA at 450 degrees C. The dc characteristics remain stable upon prolonged annealing at 450 degrees C for 45 min. This high thermal budget non-gold ohmic contact is suitable for Si-CMOS integration and enables the potential for hybrid III-V CMOS technology for 5G and mm-wave applications.